THE USE OF DIGITAL FORENSICS IN REVEALING INFORMATION AND ELECTRONIC TRANSACTION (ITE) CRIMES - Agung Ahmad Sulton Saputra; Heni Susanti (Proceeding International Conference on Social Sciences, 2026)
Currently, the most common crimes in society are the manipulation and fabrication of digital evidence. The use of digital forensics to spread disinformation or hoaxes can be carried out by anyone. These crimes can occur due to several main factors related to the development of digital technology, regulations, the political situation, and understanding of the internet world. Information and Communication Technologycrimes can also occur due to a combination of technological developments, lack of digital literacy, economic motives, regulatory weaknesses, and the existence of security holes in digital systems. Therefore, preventing information and communication technology crimes requires a cooperative approach, including increasing digital literacy, strengthening regulations, improving information and communication technology security systems, and international cooperation in enforcing digital law. From the results of the author's research, in handling cases of crime in the field of Information and Electronic Transactions, digital evidence has a legal standing as evidence even though it is not explicitly mentioned in the Criminal Procedure Code, with further regulations in the ITE Law that recognizes the validity of digital evidence such as electronic information, electronic documents, hardware and software. Success in digital forensic analysis requires strict procedures in the collection, analysis of deleted data, and metadata recovery, with the aim of maintaining the authenticity of the evidence. To optimize the use of digital forensic tools, such as UFED Cellebrite, in the Riau Regional Police, it is necessary to improve human resource competency through training and certification, optimize the use of devices by utilizing advanced features, and collaboration with other institutions.